The comparison of FOLFOX regimens with different doses of 5-FU for the adjuvant treatment of colorectal cancer: a multicenter study - DANE, FAYSAL (SPRINGER, 2021)
Purpose We aim to compare the efficiency and toxicity of three different 5-fluorouracil (5-FU) administration types in 5-FU, leucovorin, and oxaliplatin (FOLFOX) combination treatment for adjuvant therapy in colorectal cancer (CRC). Methods Five hundred and seventy patients with stage III colorectal carcinoma who received different FOLFOX regimens after curative resection were included. Patients were divided into three groups as FOLFOX-4, modified FOLFOX-6 (mFOLFOX-6), and mFOLFOX-4 for comparison of toxicity and disease-free survival (DFS) and overall survival (OS) times. Results Three-year DFS rates for FOLFOX-4, mFOLFOX-6, and mFOLFOX-4 groups were 65%, 72%, and 72%, respectively. Five-year OS rates for FOLFOX-4, mFOLFOX-6, and mFOLFOX-4 groups were 69%, 75%, and 67%, respectively. There was no statistically significant difference between the three treatment groups in terms of DFS and OS (p = 0.079, and p = 0.147, respectively). Among grade 1-2 adverse events (AE), thrombocytopenia, neuropathy, and stomatitis were more common in the mFOLFOX-6-treated group. The frequency of grade 1-2 nausea and vomiting were similar in mFOLFOX-6 (36.3% and 24%, respectively) and mFOLFOX-4 (32.4% and 24.7%, respectively) groups but were higher than that in the FOLFOX-4 (19.5% and 11.3%, respectively) group. Among the most common grade 3-4 AE, neutropenia (53.4%, 9%, and 13.5%, respectively) and diarrhea (10.5%, 2.2%, and 2.4, respectively) were more common in FOLFOX-4. The rate of anemia and febrile neutropenia was similar in treatment groups (p = 0.063, and p = 0.210, respectively). Conclusion In the adjuvant treatment of stage III CRC patients, three different 5-FU administration types in FOLFOX combination treatment can be used with similar efficiency and manageable toxicity.
Keywords: Adjuvant chemotherapy; Colorectal cancer; FOLFOX regimens; Stage III